2015
DOI: 10.1589/jpts.27.1719
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of isometric shoulder muscle strength measurement with a handheld dynamometer and belt

Abstract: [Purpose] The aim of this study was to develop a method of measuring isometric shoulder joint muscle strength using a handheld dynamometer with a belt and investigate its test-retest reliability. [Subjects] The subjects comprised 40 healthy adults. [Methods] Six types of isometric shoulder muscle strength were measured twice, and reliability was assessed. [Results] The intraclass correlation coefficient (1, 1) values ranged from 0.976 to 0.902. The result of a Bland-Altman analysis showed differences in the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 3 publications
0
30
3
1
Order By: Relevance
“…Previous studies performed two different isometric shoulder extensor strength measurements, one with the shoulder 0° flexed and abducted with the participant in a sitting position11 ) , and one with the shoulder 90° flexed with the participant in the supine position12, 13 ) . In other studies10, 14 ) , isometric shoulder internal rotator strength measurement was performed in all kinds of positions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed two different isometric shoulder extensor strength measurements, one with the shoulder 0° flexed and abducted with the participant in a sitting position11 ) , and one with the shoulder 90° flexed with the participant in the supine position12, 13 ) . In other studies10, 14 ) , isometric shoulder internal rotator strength measurement was performed in all kinds of positions, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of HHD for assessing shoulder strength has been investigated previously, but the studies have used various shoulder positions. Some studies 10 , 11 ) have suggested that HHD for assessing shoulder strength is highly reliable. Commonly, isometric shoulder extensor strength is assessed in the seated position with the shoulder in the 0° flexed and abducted position 10 ) , or in the supine position with the shoulder in the 90° flexed position 2 , 3 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies 10 , 11 ) have suggested that HHD for assessing shoulder strength is highly reliable. Commonly, isometric shoulder extensor strength is assessed in the seated position with the shoulder in the 0° flexed and abducted position 10 ) , or in the supine position with the shoulder in the 90° flexed position 2 , 3 ) . Bohannon et al reported intra-rater reliability (ICC 3, 1 ) mean values of 0.974 for the dominant side, and 0.973 for the non-dominant side, for supine subjects with the shoulder in the 90° flexed position.…”
Section: Discussionmentioning
confidence: 99%
“…Various movements of joints at different angles produce various postures. The efficiency of movements varies according to the angles between the bones and origin and insertion 23 ) . Absolute muscle force, joint angle during measurement, and the length of force applied from the joint axis affects the expressed muscle strength 24 ) .…”
Section: Discussionmentioning
confidence: 99%